2009
DOI: 10.1007/s00224-009-9240-4
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Sum-Tests and Independence Tests

Abstract: We study statistical sum-tests and independence tests, in particular for computably enumerable semimeasures on a discrete domain. Among other things, we prove that for universal semimeasures every 0 1 -sum-test is bounded, but unbounded 0 1 -sum-tests exist, and we study to what extent the latter can be universal. For universal semimeasures, in the unary case of sum-test we leave open whether universal 0 1 -sum-tests exist, whereas in the binary case of independence tests we prove that they do not exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In [2] it is shown that the function E is upper semicomputable, D(x, y) = E(x, y) + O (log E(x, y)), the function E is a metric (more precisely, that it satisfies the metric (in)equalities up to a constant), and that E is minimal (up to a constant) among all upper semicomputable distance functions D satisfying the mild normalization conditions y: y =x 2 −D (x,y) 1 and…”
Section: Preliminariesmentioning
confidence: 96%
See 1 more Smart Citation
“…In [2] it is shown that the function E is upper semicomputable, D(x, y) = E(x, y) + O (log E(x, y)), the function E is a metric (more precisely, that it satisfies the metric (in)equalities up to a constant), and that E is minimal (up to a constant) among all upper semicomputable distance functions D satisfying the mild normalization conditions y: y =x 2 −D (x,y) 1 and…”
Section: Preliminariesmentioning
confidence: 96%
“…(Here and elsewhere in this paper "log" denotes the binary logarithm.) It should be mentioned that the minimality property was relaxed from the D functions being metrics [2] to symmetric distances [10] to the present form [11] without serious proof changes. The normalized information distance (NID) e is defined by…”
Section: Preliminariesmentioning
confidence: 98%
“…As a corollary of Proposition 3 it follows that: By [7] every lower semicomputable sumtest for m is bounded by a constant, which implies that if d was lower semicomputable, than d + 0, and thus only the constant e = 0 is allowed.…”
Section: ⊓ ⊔mentioning
confidence: 94%
“…x BB(k)}. It is a very slow growing function, dominated by any unbounded non-decreasing function [7].…”
Section: Sophistication and Coarse Sophisticationmentioning
confidence: 99%
See 1 more Smart Citation